EXPLORING PRE-SERVICE ENGLISH TEACHERS’ PERSPECTIVES ON THE IMPLEMENTATION OF ASSESSMENT FOR LEARNING IN INTENSIVE READING INSTRUCTION - Aisyah,; Suseno, Muchlas; Setiadi, Samsi (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study investigates the pre-service english teachers’ perspectives on assessmengt for learning in intensive reading. It identifies key challenges faced by students, including difficulty in finding the main idea of paragraphs, interpreting text content due to limited vocabulary, and low motivation to read. Additionally, the study emphasizes the lack of structured assessments, making it difficult for lecturers to monitor students' progress effectively. The research underscores the importance of reading assessments in academic development, highlighting various assessment tools and strategies that can improve reading proficiency. By addressing gaps in current practices, the study aims to enhance the effectiveness of reading assessments and ultimately improve learning outcomes for students​.